2019
DOI: 10.3390/rs11172013
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Root Zone Soil Moisture Across the Eastern United States with Passive Microwave Satellite Data and a Simple Hydrologic Model

Abstract: Root zone soil moisture (RZSM) affects many natural processes and is an important component of environmental modeling, but it is expensive and challenging to monitor for relatively small spatial extents. Satellite datasets offer ample spatial coverage of near-surface soil moisture content at up to a daily time-step, but satellite-derived data products are currently too coarse in spatial resolution to use directly for many environmental applications, such as those for small catchments. This study investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 80 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…However, the MW-based SM measurements only account for the top few (∼0-5) cm of the soil column. There have been multiple studies exploring the assimilation/ forcing of the surface SM data from MW sensors into LSMs and crop models with some success in reducing the model errors (Bolten and Crow 2012, Ridler et al 2014, Lievens et al 2015, Yang et al 2016, Baldwin et al 2017, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…However, the MW-based SM measurements only account for the top few (∼0-5) cm of the soil column. There have been multiple studies exploring the assimilation/ forcing of the surface SM data from MW sensors into LSMs and crop models with some success in reducing the model errors (Bolten and Crow 2012, Ridler et al 2014, Lievens et al 2015, Yang et al 2016, Baldwin et al 2017, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the water exchange happens immediately and ends within one day when soil water in the first layer exceeds field capacity, with an infinite permeability. Third, the soil water loss of the second layer decreases linearly from a relatively humid (does not include the real humid condition with a significant non-linear water loss function) condition to the wilting point [24,29,52].…”
Section: (D) Soil Moisture Analytical Relationship (Smar) Modelmentioning
confidence: 99%
“…However, based on the non-linear relationship between SSM and RZSM [26], it is possible to estimate RZSM that is based on SSM data. The RZSM can be estimated from SSM by using filtering techniques [28] and analytical models [24,29]. Furthermore, Cumulative Distribution Function (CDF) matching could be used to derive RZSM with the depth scaling method [30].…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing SSM observations have been assimilated or used as forcing into different land surface models (LSM) and crop models, in order to derive RZSM, with the model errors being partially reduced [21][22][23][24][25][26]. Nevertheless, the studies reported that using SSM alone is limited by the disconnection between surface and subsurface dynamics, which in turn leads to uncertainties in the root-zone model.…”
Section: Introductionmentioning
confidence: 99%